EFEK PEMAKAIAN ALAT ORTHODONSI CEKAT TERHADAP TINGKAT PERCAYA DIRI MAHASISWA PADA TIGA ASRAMA DAERAH DI YOGYAKARTA - Dwi Nur Agustini; Susilarti Susilarti; Ta’adi Ta’adi (Poltekkes Kemenkes Yogyakarta, 2014)
The condition of irregular teeth in the oral cavity such as crowding, crookedteethor teeth rarely can cause a variety of problems among others, disrupting thefunction of mastication, speech function and appearance and selfconfidence.Orthodontic appliance fixed is a tool affixed to the teeth that fixing andlooseby specialist dentist orthodonti which functioning to balance the face so balancedand harmonious, more stable position ofteeth, masticatory function be betterand restore self confidence. The Purpose of this study is to know the Efect betweenthe use offixed orthodontic appliance the level of self-confidencein college studentson three dormitory area in Yogyakarta. This research is an analytical survey withacross sectional study. The research is done in three dormitory area in Yogyakarta.The sample in this research is all college students in the three dorm area in Yogyakartawho use orthodontic appliance fixed then measure the level of confidence using aquestionnaire sheet. Analysis of test data using statistical Chi Square with a 0.05significance level. The results of cross tabulation with the use of fixed orthodonticappliance with self confidence level shows the level of self confidence before andafter the use of different fixed orthodontic appliance where there is arise in the numberof respondents with a high level of self confidence after using the appliance fixedorthodontics of 11 respondents (50%) to 22 respondents (90.9%) and there was adecrease in the number of respondents with a low level of self confidence that is of 11respondents (50%) to 2 respondents (9.1%). Test with a Chi Square test statisticsobtained ñ value 0.003 with a significance value of 0.05.There is a Effect of fixed orthodontic appliance usage to the level of self confidencein the student dormitories in three areas in Yogyakarta